The mechanical support of cardiogenic shock. Issue 4 (August 2021) - Rob, Daniel; Bělohlávek, Jan
Abstract : Purpose of review: Cardiogenic shock (CS) therapy involving catecholamines, inotropes, fluids and revascularization is often insufficient, and short-term mortality remains 50%. Different treatment algorithms and mechanical circulatory support devices (MCS) have been increasingly used in the treatment of CS. Coronavirus disease 2019 (COVID-19) pandemic is a major challenge faced by intensive care medicine providers inevitably influencing also CS management. Recent findings: There is a lack of prospective data as well as international consensus regarding CS classification, patient risk stratification, and MCS use. Veno-arterial extracorporeal membrane oxygenation is considered the first line MCS in refractory CS and Impella the MCS of choice for the left ventricle unloading. Several ongoing randomized trials will provide much-needed evidence for MCS use in the coming years. COVID-19 infection is associated with several cardiovascular disorders complicated by CS and more data regarding the prevalence and mortality of CS during COVID-19 infection are needed. Summary: This review summarizes current trends in the use of MCS in CS and discusses differences in CS management during the COVID-19 pandemic. Careful patient selection, early MCS initiation, and comprehensive intensive care by experienced team is key to successful outcome in patients with refractory CS.